Prevalence and correlates of cigarette smoking among Dulong adults in China: A cross-sectional survey in 2020 - Ying Shao; Shun Zha; Mingfang Qin; Qiuyan Zhu; Xiliang Yang; Cangjiang Yang; Xinlin Wang; Yanli Zhang; Weimei Yang; Kunhua Zhou; Yanmei Li; Xian Tang; et al. (Frontiers Media S.A., 2022)
BackgroundThe Dulong people are one of the minorities in China with the lowest population. In recent years, the lifestyle of the Dulong people has also changed drastically due to income growth and urbanization. This study aims to identify cigarette smoking prevalence and potential risk factors among Dulong adults in China.MethodsThis study was conducted among 1,018 adults based on the Dulong Health Status Investigation and Evaluation (DHSIE) in Gongshan Dulong and Nu Autonomous County of Yunnan province, Southwest China. A cross-sectional design and face-to-face questionnaire were used to collect cigarette smoking habits and demographic information. Data were weighted by post-stratification weights according to the age and gender composition of Dulong resident. We also analyzed univariate and multivariate unconditional logistic regression to explore current smoking correlates.ResultsThe weighted prevalence of ever-smoking, currently smoking, and formerly smoking among Dulong adults is 31.3, 27.7, and 3.6%, respectively. The prevalence of ever-smoking and currently smoking among male participants (57.0 and 50.6%) is much higher than that of female participants (4.0 and 3.4%). Nearly 60% of ever-smokers and current smokers smoked more than 20 cigarettes per day, which are higher than former smokers (35.2%). Among current smokers, 33.1% relapsed, and 28.3% intend to quit smoking. By adjusting for potential confounding variables, multiple logistic regression analysis indicated that male participants (OR = 48.982, 95% CI: 25.026-95.869) and current drinkers (OR = 4.450, 95% CI: 2.556-7.746) are more likely to be current smokers. On the contrary, current smokers are also more likely to be exposed to secondhand smoke (OR = 4.269, 95% CI: 2.330-7.820) and have a higher risk of chronic respiratory disease (OR = 4.955, 95% CI: 1.669-14.706).ConclusionCigarette smoking is highly prevalent among the Dulong people in Southwest China. An appropriate and effective tobacco control strategy is an urgent need for this population.